Out-of-Pocket Costs for Colposcopy Among Commercially Insured Women From 2006 to 2019. Issue 1 (January 2022) - Fendrick, A. Mark; Dalton, Vanessa K.; Tilea, Anca; Malone, Anita M.; Moniz, Michelle H.
Abstract : Out-of-pocket costs for women who undergo colposcopy are common, significant, and have increased over time.